Lending structure and 3-factor CAPM risk exposures: the case of Malaysia - Aisyah Abdul Rahman,; Mansor H. Ibrahim,; Ahamed Kameel Mydin Meera, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study addresses the linkages between lending structure and bank risk exposures via the Capital Asset Pricing Model (CAPM). Based on the 3-factor CAPM, five risk measures are examined; namely, the market, interest rate, exchange rate, total and unsystematic risk exposure. The influence of lending structure is analysed via four measures, the real estate lending, the specialisation index, the short-term lending stability, and the medium-term lending stability. Our findings show that the lending structure affects the market, interest rate, and unsystematic risk exposures. The stability of lending structure in both the short-term and medium-term period positively influence the market and interest rate risk exposure. On the other hand, the medium-term lending structure stability negatively affects the unsystematic risk exposure. Thus, the policy makers, bankers, and investors should not ignore the significant role of the lending structure when developing a strategic risk management framework